Carbon quantum dots in hard carbon: An approach to achieving PIB anodes with high potassium adsorption. (15th April 2022) - Guo, Yuanyuan; Feng, Yefeng; Li, Hao; Wang, Yao; Wen, Zhen; Zhou, Guofu
Abstract: Potassium ion batteries have become one of the most promising candidates for Lithium batteries replacement. Here we report a carbon quantum dots@hard carbon (CQDHC) composite electrode material for PIBs that was fabricated by a one-step low-temperature pyrolysis process for the first time. Without complicated post-processing steps, the as-obtained CQDHC can be directly used as a negative potassium electrode. The oxygen-rich carbon quantum dots (CQDs) were in-situ synthesized and randomly located in the hard carbon matrix, enhancing the disorder of CQDHC and promoting potassium adsorption. As a result, the initial charge capacity reaches 361 mAhg −1 and maintains a capacity of 237 mAhg −1 (75.7%) after 150 cycles at 100 m A g −1 . The CQDHC electrode also shows long-term stable charge-discharge reproducibility and high columbic efficiency (97%). Even though with low surface area, the CQDHC electrode still offers better rate performance than most of hard carbon materials owing to the synergy effect of carbon quantum dots. The detailed, quantitative analysis of the K + storage process reveals the dual-mechanism in carbon quantum dots@hard carbon. The present study sheds light on using carbon quantum dots to enhance the performance of carbon electrodes in potassium ion batteries. Graphical abstract: Image 1